Strengthening Women's Rights among Students: Case Study at The Pondok Pesantren of Tahfidz al-Qur'an Ebqory Jember - Amin Fadlillah; Ibanah Suhroardiyah Shiam Mubarokah (An-Nisa': Jurnal Kajian Perempuan dan Keislaman, 2022)
Accumulatively, the number of female students who stay in Islamic boarding schools in Indonesia is higher than that of male students. However, the reality is that this fact is not directly proportional to the existence of education to strengthen the rights of female students in Islamic boarding schools along with the curriculum and educational materials of Islamic boarding schools that tend to position women as male objects. This can be seen by teaching the Kitab Uqud al-Lujjain which is considered not to reflect gender equality. This article aims to examine the methods used by Pondok Pesantren Tahfidz al-Qur'an Ebqory Jember on the issue of strengthening women's rights among students. This study uses a qualitative research method in which data related to the object of research are obtained through in-depth observation, interviews, and literature review. This data was then analyzed and written descriptively-critically which resulted in a clear conclusion. The results of this study indicate that the strategy of strengthening women's rights in Ebqory is carried out by two methods, namely theoretically and practically. Theoretically, strengthening women's rights is done by studying the Kitab Sittin al-Adliyah, a kitab that discusses 60 authentic hadiths about the position of women in Islam and gender studies training. Practically, students are provided with individual skill training such as training as a host and cooking training.